2019
DOI: 10.1002/jbm.b.34413
|View full text |Cite
|
Sign up to set email alerts
|

Biological acellular pericardial mesh regulated tissue integration and remodeling in a rat model of breast prosthetic implantation

Abstract: The use of biological meshes has proven beneficial in surgical restriction and periprosthetic capsular contracture following breast prosthetic‐reconstruction. Three different types (smooth, texturized, and polyurethane) of silicone round mini prostheses were implanted under rat skin with or without two different bovine acellular pericardial biological meshes (APMs, BioRipar, and Tutomesh). One hundred eighty‐six female rats were divided into 12 groups, sacrificed after 3, 6, and 24 weeks and tissue samples inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 35 publications
3
8
0
Order By: Relevance
“…The inflammatory response observed after implantation of the ABP matrix was of the chronic type, with a predominance of mononuclear cellular infiltrate, compatible with the type of inflammation observed in the evaluation of biomaterials in vivo (Santos et al, 2021;Al-Maawi et al, 2017;Miguel et al, 2013;Anderson et al, 2008). This finding is in line with the study of Bernardini et al (2020) who also observed chronic inflammation after ABP implantation. However, these authors studied this biomaterial with different analysis periods than our study.…”
Section: Discussionsupporting
confidence: 88%
“…The inflammatory response observed after implantation of the ABP matrix was of the chronic type, with a predominance of mononuclear cellular infiltrate, compatible with the type of inflammation observed in the evaluation of biomaterials in vivo (Santos et al, 2021;Al-Maawi et al, 2017;Miguel et al, 2013;Anderson et al, 2008). This finding is in line with the study of Bernardini et al (2020) who also observed chronic inflammation after ABP implantation. However, these authors studied this biomaterial with different analysis periods than our study.…”
Section: Discussionsupporting
confidence: 88%
“…Bernardini et al published a paper in 2019 [28], in which they analyzed tissue remodeling occurring after implantation of two different bovine pericardiumderived biological meshes BioRipar ® (ASSUT EUROPE, Rome, Italy), and Tutomesh ® (Tutogen Medical Gmbh, Neunkirchen am Brand, Germany) and three different types (smooth, texturized and polyurethane) of minisilicone round prosthesis in a rat model. Mechanical properties of the two meshes were previously compared by using two mechanical tests, namely uniaxial tensile test and burst test, and the BioRipar ® mesh demonstrated to be more extensible and resilient than the commercial control ones [29].…”
Section: Discussionmentioning
confidence: 99%
“…Results from rat model suggested that differences in composition and/or structure of AMP likely influence tissue remodeling after their implantation alone or in combination with different prostheses. The authors concluded that additional studies were needed in order to develop a new biological mesh capable to further reduce prostheses-induced adverse events, like postsurgical periprosthetic fibrosis, following breast reconstruction [28].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Masson's trichrome-staining was performed to assess the collagen and elastic composition of the meshes and possible changes over the time after implantation. Masson's trichrome-staining intensity was arbitrarily scored on a scale of four grades: 0= negative, 1= weak positivity, 2= moderate positivity, 3= strong positivity (28).…”
Section: Morphological and Histomorphometric Analysismentioning
confidence: 99%